A framework for exploring futures of complex urban energy systems - Basu, Sumedha; Bale, Catherine S. E. (Frontiers in Climate, 2023)
In order to address the climate crisis and provide citizens with clean, secure and affordable energy, urban energy systems need to transition. This is significant as urban energy systems are increasingly seen as complex systems for their close interactions with the local urban society while being interdependent on higher levels of governance. Decisions taken today will continue to influence the inhabitants of our cities for well over 50 years while locking in the energy consumption patterns of the future. How then do we make decisions on the interventions needed to bring about a desirable future and prepare for the probable and possible futures. In this paper, we consider the key characteristics of urban energy systems from a complexity science perspective in order to explore what methodologies in futures and foresight scholarship could be beneficial in supporting urban energy decision-making. To do this we have undertaken an integrative review — a method that allows review, synthesis, critique, and analysis of new and emerging topics across multiple disciplines and multiple literature types — and consider the findings in light of their usefulness in understanding complex systems, which are inherently uncertain. We consider how futures and foresight theories and methods can be applied in urban and energy studies, highlighting examples of where around the world these have been applied by organisations seeking to shape transitions. The many methods and approaches that exist under the futures umbrella have not been applied to anything near their full potential in urban energy studies, despite the limitations of many of the planning and modelling exercises currently used. We use key learnings from existing futures and foresight scholarship, along with our understanding of urban energy systems as complex adaptive systems, to propose a theoretical and practical framework for exploring their futures. The framework encompasses concepts of futures, contextualisation, mapping uncertainty, participatory processes, and futures governance. Although there is much further research work needed to test and operationalise this framework in an applied way with city stakeholders, we hope this charts a way forward in addressing the critical challenges faced by urban energy planners and their partners.